Analysis of knowledge about acute granular pharyngitis among Tiruchirapalli school children and their parents: connotation for preventing further complications - Kanagaraj, Rajesh; Nagarajan, Prabhusaran; Syed, Mohamed Marzuk; Antony, Jesudoss (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Identification and appropriate treatment for the streptococcal pharyngitis decreases the risk of acute rheumatic fever and rheumatic heart disease. By understanding the public perceptions and behaviors related to sore throat is considered as the fundamental for disseminating the health programs to control such diseases. The main objective of this study is to understand the epidemiology and microbiology of acute granular pharyngitis and its treatment in a tertiary care teaching hospital of South India. Methods: This is a prospective and cross-sectional investigation performed by direct interview and written surveys. In this study, school students and their parents were interviewed about the history of sore throats in the last 12 months and treatment received. A focused history and physical examination to detect pharyngitis was conducted and children were referred for follow-up as indicated. Results: A total of 1550 and 1450 students from 13 and 14 schools participated in the study respectively, along with their parents. Three hundred and thirty six (21.6%) parents reported their child had at least one episode of sore throat in the previous year, and 326 (21%) of students reported at least one sore throat in the same time period. Conclusions: Girls were reported to have high level of pharyngitis than boys. Parents have variable knowledge about the frequency of sore throat in their children and its management. These results provide insight into current perceptions and practices related to sore throat and will be used to design public awareness activities aimed at reducing the future risks.